多年度ステレオ写真解析による過去半世紀の南極氷床縁変動の追跡 - 澤柿 教伸 (2016)
研究成果の概要 (和文) : 本研究は，空中写真と衛星画像という2種類のリモートセンシングデータから数値標高モデルを生成・比較することで，南極・宗谷海岸における過去45年間の氷床の表面高度変化を検出することを目的として実施した．その結果，南極・宗谷海岸地域を撮影した1960年代以降のステレオペア画像のカタログ化を完了した．実際にラングホブデ地域において氷床の表面高度変化と末端の前進を解析した結果，ラングホブデ氷河が，末端位置を1975年から2007年にかけて大きく後退させた一方，表面高度は定常状態もしくはわずかに増加傾向であったことがあきらかとなった． 研究成果の概要 (英文) : This study aims to detect in the marginal fluctuation of the Antarctic ice sheets of the past 45 years long the Soya Coast, by comparison of two types of digital elevation models of aerial photographs and satellite images. As a result, the catalog of the stereo pair images of since the 1960s, covering this region has been completed. The actual result of the analysis of the surface elevation change and the terminus position of the Langhovde glaciers shows that its terminal position is retreated significantly from 1975 to 2007, while surface elevation was slightly increased or steady state.